2011
DOI: 10.1016/j.jus.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic ultrasonography: A new method for the work-up of patients with dyspnea

Abstract: Objective: Differential diagnosis of dyspnea is vital for the management of respiratory failure, where routine parameters can now be integrated with thoracic ultrasound data. The objective of this study was to evaluate the validity and accuracy of this approach in a department of internal medicine. Materials and methods: We enrolled 152 patients consecutively hospitalized with a diagnosis of dyspnea. After clinical evaluation, chest radiography, biochemical assays (NT-proBNP), and emergency treatment, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 10 publications
3
53
0
Order By: Relevance
“…After removing the duplicate studies and the studies that did not fulfill the inclusion criteria, 8 studies were included in the meta-analysis (1301 patients; Table I) [10][11][12][13][14][15][16][17]. Two studies were performed in the ICU, three studies in the ED, two studies in the ward and one study in a pre-hospital setting and ED.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing the duplicate studies and the studies that did not fulfill the inclusion criteria, 8 studies were included in the meta-analysis (1301 patients; Table I) [10][11][12][13][14][15][16][17]. Two studies were performed in the ICU, three studies in the ED, two studies in the ward and one study in a pre-hospital setting and ED.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies diagnosed the PE by detecting B-line in anterior and lateral chest and three or more B-lines in at least two zones on each hemithorax [12,13]. Another two studies followed comet-score scanning protocol for diagnosis of PE [11,17]. The QUADAS-2 quality assessment revealed that quality of the included studies was from moderate to high (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both lung [18, 19] and vascular ultrasound [2022] have been shown to be helpful in the assessment of undifferentiated dyspnea and in the diagnosis of heart failure. It is not clear how POCUS findings change with treatment.…”
Section: Introductionmentioning
confidence: 99%